(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the effectiveness of Income Tax Article 25 collection on the compliance of corporate taxpayers in Indonesia. Article 25 income tax is an installment tax payment mechanism paid periodically by taxpayers to ease the year-end tax burden. This research uses a descriptive qualitative method with a literature review approach and analysis of secondary data from the Directorate General of Taxes. The findings reveal that the effectiveness of Article 25 tax collection is significantly influenced by the quality of tax administration systems, taxpayer understanding, and government incentive policies. Although there has been a trend of increasing formal compliance, challenges such as limited outreach and the complexity of installment calculations remain obstacles. The study recommends enhancing tax education and improving the tax information system as strategic steps to boost optimal taxpayer compliance. Keywords: Income Tax Article 25, Taxpayer Compliance, Collection Effectiveness, Corporate Taxpayers, Tax Policy